The Prevalence Of Obesity In Primary Schools Of Golestan Province Of Iran - Gholam Reza veghari; Reza Rahmati (Tehran University of Medical Sciences, 2012)
Background and Aim: Underlying factors of Obesity is various and the main aim of this study was to evaluate the prevalence of obesity and some socio-demographic related factors among Iranian northern primary school children in year 2010. Materials and Methods: This is a crossectional-descriptive study that was performed on 7399 primary school children (3934= male and 3465=female) from 112 schools that were chosen by two step sampling (cluster and simple random). The number schools were equal with respect to residential area and sex. Center of Disease Control and prevention (CDC) criteria was used for comparing anthropometric indexes. Results: Linear regression analysis revealed that weight, height and BMI increase 2.70 kg, 4.62 cm and 0.42 kgm-2 in boys (P=0.001) and 3.12 kg, 5.19 cm and 0.52 kgm-2 in girls (P=0.001) in each of years, respectively. Highest and lowest obesity was observed in Gomishan and Ramian districts, respectively. Results of logistic regression analyses showed that the risk of overweight and obesity was 1.203 times in male as compared to females[1.078-1.341, CI 95%], 1.382 times in urban as compare to rural areas[1.240-1.541, CI 95%] and 2.297 times in high economic group as compared to low economic group[1.911-2.761, CI 95]. Conclusion: Obesity was a health problem in primary school children in Golestan province and urbanization and rise of economic status was a risk factor.